Behavior of offshore dike using non-uniform geotextile mats on clay-overlaying-sand soil deposits. Issue 12 (2nd December 2021) - Zhou, Mi; Deng, Huiqi; Han, Zejun; Wang, Xiaoliang; Zhang, Xihong; Zhao, Huihui
Abstract: This paper performs finite element (FE) analysis to investigate the behaviour of a large geotextile mat offshore dike on clay-overlaying-sand soil deposits, which is reinforced by a new type of non-uniform thick geotextiles technique. A FE model is generated and validated against laboratory centrifuge testing data. A comprehensive parametric study is then conducted to examine the influences of soil properties for sand and clay, dam base width, tensile capacity of geotextile, and slope gradient of the dike. Two types of failure mechanisms, i.e. local failure and global failure are observed for large geotextile mat dikes on clay-overlaying-sand soil deposits, which are affected by the squeezing effect of the underlaying sand layer. Empirical formulae are derived based on the numerical results. A design method is then proposed for predicting the maximum tolerable fill height of the large geotextile mat dike on clay-overlaying-sand soil deposit, and to access the stability of the dike.